Manejo integrado de sigatoka negra mycosphaerella fijiensis m. en banano zona el Guabo - Dominguez Loja, Luis Humberto (2008)
During the season of May to Agosto/08 in the Treasury "Potreo", enclosure Chontillal of the caton Guabo, one investigates on the integrated control of the black Sigatoka, for that which you/they thought about the following objectives:1. To determine the effects of the handling integrated for the control of black Sigatoka (Mycosphaerella fijiensis M.), 2. To carry out an economic analysis of the treatments to use for the handling of Sigatoka quarter note (Mycosphaerella fijiensis M.). The Products included in the investigation were: Bacterias EM, rue Extracts, Timorex (terpenos), The pruning of sections of the burnt leaves or necrosadas with the illness and I eat witness fungicidal Bankit (azoxystobin). The products in mixture with agricultural oil and the respective emulsificantes were applied with a neblinadora using 32 liters approximately for hectare. In a banana tree plantation Cavendish five strips 15 meters wide were defined by 60 separated for air of reduction to avoid the one it shovels of the fungicides. The Design experimental employee was the Completely Randomizado with five treatments and six repetitions. The analyzed variables were, I number from functional leaves to the floración, initial percentage of the infection, weekly Percentage of infections, Index of severity, and functional Leaves to the crop. The variance analyses in the six atomization cycles evidenced that fungicidal Timorex, was relatively superior that Bankit and the treatments with Bacterias, rue extracts and the Pruning or surgery of the air necrosadas. However when considering the final effects in the area to foliate healthy, Bankit presents the best average of healthy leaves to the crop, 7.16. The Bacterias BM, the rue extract, they were not superior in statistical terms that the Pruning, consequently, the indexes of sigatoka infection were higher, accompanied in more area loss to foliate to the crop.